2005
DOI: 10.1002/pssb.200541104
|View full text |Cite
|
Sign up to set email alerts
|

Optical anisotropy and gas sensing properties of ordered porphyrin films

Abstract: Ordered films of porphyrins are routinely obtained by Langmuir-Blodgett technique, with a thickness control at the level of a single monolayer. The study of their optical anisotropy by reflectance anisotropy spectroscopy (RAS) has evidenced an interesting modification of the spectral line shape around the Soret band of the porphyrin layer after a certain critical thickness has been deposited onto the substrate. This finding has been connected to a structural modification of the film, although a detailed model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In our previous experiments with ethanol, we have shown that this change is not permanent: the original RAS signal can be recovered after purging the layer in nitrogen flux for several minutes [10]. But in other cases (an example is reported here), the modification of the RAS spectrum is permanent.…”
Section: Introductionmentioning
confidence: 49%
See 2 more Smart Citations
“…In our previous experiments with ethanol, we have shown that this change is not permanent: the original RAS signal can be recovered after purging the layer in nitrogen flux for several minutes [10]. But in other cases (an example is reported here), the modification of the RAS spectrum is permanent.…”
Section: Introductionmentioning
confidence: 49%
“…It has been already demonstrated that LB and LS porphyrin thin films show evident changes in their optical anisotropy spectra when exposed to VOCs [10]. Moreover, the interaction of porphyrins with some specific compounds (ethanol, in Ref.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Exposure to alcohol has been already demonstrated to lead to detectable variations of the anisotropy signal in the visible-UV region in porphyrins [37]. Monitoring the RAS response of the H 2 TPP and ZnTPP nanowires during exposure to ethanol and butanol permits checking the strength and characteristics of the interaction resulting with these porphyrins when they are in the form of crystalline nanowires with the specific structure.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of metal ions and peripheral substituents on the organization of porphyrin supramolecular assemblies at the air-water interface and their transfer onto solid supports have been thoroughly investigated [75][76][77][78][79][80]. The ultra-thin films prepared by these methods were also widely used for detection of gases or volatile organic compounds (VOCs) in gaseous phase [72,79,[81][82][83][84][85][86]. It is somewhat surprising however, that this great effort devoted to the preparation of sensing monolayers has generated only a few examples of porphyrin-based sensors operating in aqueous solutions [87].…”
Section: Introductionmentioning
confidence: 99%